Cellular glutathione content in the organ of Corti and its role during ototoxicity - Majumder, Paromita; Duchen, Michael R.; Gale, Jonathan E. (Frontiers in Cellular Neuroscience, 2015)
Glutathione (GSH) is the major scavenger of reactive oxygen (ROS) inside cells. We used live confocal imaging in order to clarify the role of GSH in the biology of the organ of Corti, the sensory epithelium of the cochlea, before, during and after the onset of hearing and in ~1 year old mice. GSH content was measured using monochlorobimane (MCB), a non-fluorescent cell permeant bimane that reacts with GSH, forming a fluorescent adduct through a reaction catalysed by glutathione-S-transferase. GSH content increased significantly in inner hair cells during maturation in young adult animals, whereas there was no significant change in the outer hair cells. However, the GSH content in inner hair cells was significantly reduced in ~1 year old mice. The GSH content of supporting cells was comparatively stable over these ages. To test whether the GSH content played a significant protective role during ototoxicity, GSH synthesis was inhibited by buthionine sulfoximine (BSO) in organotypic cochlear explant cultures from immature mice. BSO treatment alone, which reduced [GSH] by 65% and 85% in inner hair cells and outer hair cells respectively, did not cause any significant cell death. Surprisingly, GSH depletion had no significant effect on hair cell survival even during exposure to the ototoxic aminoglycoside neomycin. These data suggest that the involvement of ROS during aminoglycoside-induced hair cell death is less clear than previously thought and requires further investigation.